Derepression of β-Galactosidase Synthesis in Escherichia coli K-12 by p-Fluorophenylalanine - Kang, Soosang (1968)
p-Fluorophenylalanine (FPA) derepresses β-galactosidase synthesis at 35 C but not at 25 C in Escherichia coli K-12, strain MC132 (lac I1,2), a strain with a temperature-sensitive lac repressor. In contrast, strain MC130 (lac I(+)) is not derepressed by FPA at 35 C. Temperature-shift experiments with strain MC132 in the presence of FPA and other reagents (isopropyl-1-thio-β-d-galactoside or chloramphenicol) are consistent with the following mechanism. FPA is incorporated into the genetically altered lac repressor at all temperatures. This further alteration due to incorporation of analogue makes the lac repressor protein inactive at 35 C but active at 25 C. Once an active tertiary structure is formed at 25 C, it is stable at 35 C. However, the inactive tertiary structure of the FPA-containing repressor can assume an active tertiary structure when the temperature is shifted from 35 to 25 C. In the discussion of the results, “inactive tertiary structure” is equated with “monomers” and “active tertiary structure” with oligomers.